Relevansi Konsep Vicarious Liability dalam Putusan No. 296/Pid.Sus/2021/PN Kdi Tindak Pidana Pertambangan - Vincentius Ake (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study analyzes the judges’ considerations in Decision No. 296/Pid.Sus/2021/PN Kdi and examines the relevance of the vicarious liability concept in corporate criminal liability for mining offenses. The case revealed that only the individual was convicted, while the corporation remained unaccountable. This research uses a normative legal method with statutory and case approaches. The results show that the judges’ considerations did not fully apply the principle of corporate criminal responsibility. Implementing vicarious liability is crucial to ensure justice and corporate accountability in mining crimes.